Historical Study of The Role of The Juang City: Bireuen For The Indonesian Independence Revolution Period - Muhjam Kamza; M Yusrizal; Mawardi Mawardi; Teuku Kusnafizal; Teuku Abdullah (Proceedings of AICS - Social Sciences, 2021)
The Aceh region became a battleground in the Dutch-Indonesian Revolutionary War of Independence, which lasted from 1945 to 1949. Bireuen, as one of Aceh's cities, became the core of the fight to stop the Dutch invasion of Indonesia. This research looks at the function of Bireuen, which has taken the jargon of